Effects of calcium hypochlorite and octenidine hydrochloride on L929 and human periodontal ligament cells - Coaguila-Llerena, Hernán [UNESP]; Rodrigues, Elisandra Márcia [UNESP]; Tanomaru-Filho, Mário [UNESP]; Guerreiro-Tanomaru, Juliane Maria [UNESP]; Faria, Gisele [UNESP] (FapUNIFESP (SciELO), 2019)
The aim of this study was to assess cytotoxicity and cell migration of calcium hypochlorite [Ca(OCl)2] and octenidine hydrochloride-OCT (Octenisept®, Schülke & Mayr, Norderstedt, Germany) in L929 and human periodontal ligament (hPDL) cells. The cells were exposed to different doses of different solutions: 2.5% and 5% Ca(OCl)2, 0.1% OCT, 2.5% NaOCl and 2% CHX for 10 min. Cell viability was assessed by methyl-thiazol-tetrazolium (MTT) and neutral red (NR) assays, and cell migration was determined by wound-healing assay. Statistical analysis was performed by two-way ANOVA and Bonferroni tests (α=0.05). The MTT and NR assays revealed that 0.1% OCT was less cytotoxic in hPDL cells (p<0.05), followed by 2% CHX and 2.5% Ca(OCl)2 (p<0.05). There was no significant difference between 2.5% NaOCl and 5% Ca(OCl)2 (p>0.05), but these solutions showed greater cytotoxicity than the others. The result was the same for L929 cells, except that there was no significant difference between 2% CHX and 2.5% Ca(OCl)2 (p>0.05). Wound-healing assay in L929 and hPDL cells showed that cell migration of 0.1% OCT, 2% CHX and 2.5% Ca(OCl)2 groups was higher than 5% Ca(OCl)2 and 2.5% NaOCl groups at 24 h (p<0.05). In conclusion, 0.1% OCT had lower cytotoxicity in tested cell lines than CHX, Ca(OCl)2 and NaOCl. Cell migration was higher for 0.1% OCT, 2% CHX and 2.5% Ca(OCl)2. Therefore, in terms of cytotoxicity, OCT and Ca(OCl)2 have the potential to be used as root canal irrigants.
Keywords: Calcium hypochlorite; Cytotoxicity; Fibroblasts; Octenidine; Root canal treatment